2012
DOI: 10.5455/vetworld.2012.359-361
|View full text |Cite
|
Sign up to set email alerts
|

Disposal and utilization of broiler slaughter waste by composting

Abstract: Aim: To know the feasibility of hygienic and environmentally safe method of disposal of broiler slaughter house waste with coir pith and caged layer manure. Materials and Methods: Compost bins (4 feet x 4 feet x 4 feet) were established with concrete blocks with air holes to facilitate aerobic composting. The broiler slaughter waste and coconut coir pith waste were collected from the local market, free of cost. The caged layer manure available from poultry farms were utilized as manure substrate. Physical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This is because it can be converted to sanitary and marketable organic fertilizer [4,5]. The stabilization process during composting kills most parasites, pathogens, and viruses contained in the livestock waste [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…This is because it can be converted to sanitary and marketable organic fertilizer [4,5]. The stabilization process during composting kills most parasites, pathogens, and viruses contained in the livestock waste [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The results are corroborate with the earlier reports of Tiquia et al [30] and Huang et al [31] who observed similar results in spent litter swine manure and saw dust. On the other hand Bharathy et al [32] recorded significantly (P<0.05) lower total nitrogen content in the finished product of compost of broiler slaughter waste. [35] in cattle manure compost without dead birds.…”
Section: Nitrogenmentioning
confidence: 91%
“…Hence, by following an integrated biorefinery approach, the byproducts of the slaughterhouse can be utilized appropriately, not only to reduce pollution (contamination) but also to create job opportunities [2]. Slaughterhouse by-products are taken to be secondary products obtained during the slaughtering and processing of livestock to get meat and by-products exist in liquid, solid, and semi-liquid forms [3,4].…”
Section: Introductionmentioning
confidence: 99%